CHANGES IN BALINESE IDENTITY AND CULTURE AS A RESULT OF TOURISM: Perubahan identitas dan budaya Suku Bali sebagai akibat dari Pariwisata - Dwianita Conny Palar; Benson Paul Hewat (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The intricate tapestry of Balinese identity is deeply intertwined with Hinduism, shaping a hierarchical societal structure organized around religious affiliations, castes, and traditional roles. While historically rigid, contemporary Balinese society exhibits a more flexible approach to identity, although Hindu influence remains pervasive. Historical shifts, including Dutch Colonization, Indonesia's independence and subsequent governance policies of the New Order, have further impacted Balinese identity, leading to major changes in Balinese social and political structures, furthermore economic factors, particularly tourism, have played a significant role, both amplifying cultural expression and triggering challenges such as over-tourism and urbanization, with implications for traditional livelihoods and environmental sustainability, The dichotomy of Sekala (perceivable) and Niskala (sacred) encapsulates the dual nature of Balinese culture, with interactions tailored differently for internal and external audiences. This study explores the impact of tourism and government policy on Balinese culture and identity, considering the historical background and economic significance of the island. Tourism being the primary industry, has caused Bali to experienced significant cultural and demographic shifts over the year, the influx of tourism has shaped Balinese society, economy, and cultural practices. Drawing on historical perspectives, writing, as well as contemporary observations the researcher seeks to use literature reviews, participant observations as well as interviews, by integrating firsthand perspectives with existing scholarship, the author aims to view, analyse and understand the impacts of Tourism and a post-colonial government has had and continues enrich and challenge Balinese culture and identity as well for this study to contribute to a comprehensive understanding of this complex phenomenon and inform future research and policymaking in the field.